Aromaterapi Lavender Menurunkan Nyeri Haid Pada Civitas Rumah Sakit: Lavender Aromatherapy Reduces Menstrual Pain in Hospital Community - Siti Eva Nurlinda; Emi Yuliza; Irma Herlina (Open Access Jakarta Journal of Health Sciences, 2022)
Introduction: Dysmenorrhea is a common complaint in women and almost all women experience it. This pain occurs at the same time as menstruation, before menstruation, or immediately after menstruation. Dysmenorrhea is pain that is felt during menstruation which causes daily activities to be disrupted. Aromatherapy is an action that can be given to women who experience menstrual pain. Objective: This study aims to examine the lavender aromatherapy intervention on menstrual pain/dysmenorrhea in RS Salak Bogor. Methods: This study uses a quantitative method with a pre-experimental design and a one-group pre-post test design with a total of 20 respondents working at Salak Hospital, Bogor. The statistical test used was the Wilcoxon test. Results: The study showed that the menstrual pain scale before intervention was a moderate pain scale (4-6) for as many as 85% of respondents, and a mild pain scale (1-3) for as many as 15% of respondents. Post-test menstrual pain scales mild pain (1-3) as many as 80% of respondents, and moderate pain scale (4-6) as many as 20% of respondents. After being given lavender aromatherapy, there was a decrease in menstrual pain/dysmenorrhea in the community of Salak Hospital, Bogor, which was indicated by a decrease in the mean value. The pre-test data obtained a value of 4.2 and decreased to 2.9 and the p-value was 0.000.). Conclusion: Aromatherapy lavender is effective in reducing the intensity of menstrual pain in the community of Salak Hospital, Bogor in 2021